2015
DOI: 10.1073/pnas.1512952113
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin functions to sterically hinder γ-secretase–substrate interactions driven by substrate transmembrane domain

Abstract: γ-Secretase is an intramembrane-cleaving protease that processes many type-I integral membrane proteins within the lipid bilayer, an event preceded by shedding of most of the substrate's ectodomain by α-or β-secretases. The mechanism by which γ-secretase selectively recognizes and recruits ectodomain-shed substrates for catalysis remains unclear. In contrast to previous reports that substrate is actively recruited for catalysis when its remaining short ectodomain interacts with the nicastrin component of γ-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
152
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(161 citation statements)
references
References 68 publications
(97 reference statements)
7
152
1
Order By: Relevance
“…In a recent study, we have demonstrated that substrates with large ectodomains have a reduced binding affinity for γ-secretase due to steric clashing with the nicastrin component of the γ-secretase complex (Bolduc et al, 2016). Based on this, and results from our current study, we might expect that γ-secretase can chose its substrates through a complex interplay between ectodomain length, helical TMD stability and the sequence of amino acids (specifically aromatic amino acids) within substrate TMD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we have demonstrated that substrates with large ectodomains have a reduced binding affinity for γ-secretase due to steric clashing with the nicastrin component of the γ-secretase complex (Bolduc et al, 2016). Based on this, and results from our current study, we might expect that γ-secretase can chose its substrates through a complex interplay between ectodomain length, helical TMD stability and the sequence of amino acids (specifically aromatic amino acids) within substrate TMD.…”
Section: Discussionmentioning
confidence: 99%
“…These include Presenilin 1 (PS1), Presenilin 2 (PS2), nicastrin, anterior pharynx defective (APH-1), and PS enhancer (PEN2) (Francis et al, 2002). PS1 and PS2 form the catalytic domain of γ-secretase while APH-1 may act as a stabilizer, PEN2 acts as a regulator/enhancer of activity, and nicastrin serves as a substrate receptor (Bolduc et al, 2016; Dries and Yu, 2008; Holmes et al, 2014). The cleavage event catalyzed by γ-secretase does not occur at a single site as there are three cleavage sites on APP separated by three amino acids; ε, γ, and δ. γ-secretase assembly, trafficking, and substrates have been reviewed elsewhere (De Strooper et al, 2012; Dries and Yu, 2008; Haapasalo and Kovacs, 2011).…”
Section: Amyloid Precursor Proteinmentioning
confidence: 99%
“…To date, all intramembrane proteases that have been analyzed are very slow enzymes, usually taking minutes (and even hours) to cleave each substrate molecule (Dickey et al, 2013; Kamp et al, 2015; Bolduc et al, 2016). As such, even trace ‘invisible’ amounts of contaminating cellular proteases can create severe interference when establishing a protease assay with such slow enzymes.…”
Section: Establishing An Inducible and Fluorogenic Intramembrane Pmentioning
confidence: 99%
“…This can be achieved with a simple set of four reconstitution reactions: the wildtype intramembrane protease assayed at pH 7.4 and at pH 4.0, and its catalytic mutant assayed at pH 7.4 (in the absence or presence of proteinase K as a positive cleavage control). For acid proteases, elevated pH instead of pH 4 is likely to be required; pH 8.5 works well in reversibly inactivating the aspartyl intramembrane protease γ-secretase (Bolduc et al, 2016). …”
Section: Establishing An Inducible and Fluorogenic Intramembrane Pmentioning
confidence: 99%